Morpho-Anatomical Changes In Gladiolus Due To Infection By Meloidogyne Incognita (Applied Biological Research, 2017)
Meloidogyne incognita is emerging as a major problem in the successful cultivation of gladiolus. The present study was aimed to study the effect  of M. incognita on some plant growth parameters of gladiolus cv.  ‘Sylvia’ and to demonstrate the histopathological changes in gladioli due  to M. incognita infestation. During the experiment, gladiolus crop was  found severely infested with M. incognita and showed significant  reduction in plant growth parameters and flower production. In severe  infestation, no flower was produced. The histopathology of plant roots  revealed that 2ndstage juveniles penetrated into root cortex and moved  along the cortical layer of cells and started feeding. During feeding  process, they produced some hypertrophied cells in vascular cylinder  and hyperplasia in pericycle regions. The hypertrophied cells were  metabolically highly active, multinucleate and contained dense  cytoplasm. In gladiolus, 4-6 such hypertrophied cells were observed in  vascular tissues and stellar region of roots. Though the site of infection  was vascular tissue but due to the nematode development and giant cell  formation, the entire nematode complex and giant cells appeared  irregular in root section. The nematodes damaged complete thickness of  roots and this condition lead to the destruction of feeder roots which  ultimately affected plant growth by reducing water and nutrient  absorption from soil.
Keywords: Meloidogyne incognita; multinucleate giant cells; second stage juvenile